Penerapan Metode Analisis Return, Repayment, dan Risk Bearing Ability dalam Penilaian Kelayakan Kredit Pensiun di PT Bank Mandiri Taspen KCP Ujung Berung - Rakhman, Faisal; Aziz, Anisa Silvana (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
Based on the preliminary study results, that the background of this research is the number of pension credit customers who have decreased, especially in 2021 and 2022, this is suspected at the time of the assessment there are customers who do not meet the conditions such as prospective customers who have the same credit at other banks, there is lack of documents such as KTP, SK, and other documents. This study aims to find out how the application of return, repayment, and risk bearing ability analysis methods in assessing pension creditworthiness at PT Bank Mandiri Taspen KCP Ujung Berung. The object of this research is to assess the creditworthiness of pensioners at PT Bank Mandiri Taspen KCP Ujung Berung. The type of research is descriptive qualitative with primary data types and uses data collection techniques in the form of observation, interviews, literature study, and documentation. While the data analysis techniques are data collection, reduction, data presentation, and conclusions. The results showed that the application of return, repayment and risk bearing ability has been carried out quite well, this is based on the number of problematic credit customers who are quite healthy. Qualitative data analysis techniques that use the Miles and Huberman, there are three things that become the basis for applying the return analysis method in assessing the feasibility of pension credit, there are four things that become the application of the repayment analysis method in assessing the feasibility of pension credit, and there are two things that become the application of the risk bearing ability analysis method in assessing the feasibility of pension credit at PT Bank Mandiri Taspen KCP Ujung Berung.